Pengaruh Literasi Keuangan, Akses Permodalan dan Minat menggunakan E-Commerce terhadap Kinerja UMKM di Kabupaten Sumbawa - Margareta, Amanda; Mandasari, Jayanti (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the influence of financial literacy, access to capital, and interest in using e-commerce on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Sumbawa Regency. MSMEs are recognized as the backbone of Indonesia's economy, contributing significantly to employment absorption and national Gross Domestic Product (GDP). However, MSME performance still faces several challenges, such as low levels of financial literacy, limited access to capital, and uneven adoption of digital technology. This research employs a quantitative approach with an explanatory design. Data were collected through structured questionnaires distributed to 100 MSME actors using stratified random sampling. The data were analyzed using multiple linear regression with classical assumption tests to ensure model validity. The results show that financial literacy has a positive and significant effect on MSME performance, highlighting the importance of cash, credit, and financial planning management skills. Access to capital has the strongest positive influence, emphasizing the vital role of funding in business expansion, innovation, and productivity. Moreover, interest in using e-commerce also has a significant positive effect, indicating that the use of digital platforms can expand market reach and improve efficiency. Overall, these findings underscore the importance of strengthening internal resources such as human capital, financial capacity, and technological adoption as key strategies to enhance the sustainability and competitiveness of MSMEs.